Implementasi Cyber Public Relations Di Pemerintahan Kabupaten Garut Melalui media sosial Instagram - Rinrin, Ade; AS, Enjang; Dulwahab, Encep (Reputation: Jurnal Ilmu Hubungan Masyarakat, 2021)
This study aims to find out how to implement Cyber Public Relations in the Garut Regency Government through Instagram Social Media. The research method used is descriptive analysis with a qualitative approach. The concept used in this research is Four Step Public Relations. The research results obtained are: Definition of the problem carried out by analysis of the media situation, and analysis of media content. Planning and program is determining the purpose and design of content, and program content. Implementation and communication, namely managing Instagram accounts, utilizing Instagram features, creating content, and Evaluation.